Disc Laser System Construction and Characterization - Abd-Alameer, Yousif H.; Dhahir, Mohamed K.; Hajim, Khalil I. (Iraqi Journal of Laser, 2010)
In this work a Nd:YVO4 thin disc laser setup is designed and fabricated. The disk laser systemis designed to be compact. The laser crystal was pumped by a 808 nm diode laser. The effect of inputcurrent and pulse frequency on the output energy at pulse operation mode, and the effect of the inputcurrent on the output power at CW mode operation are tested. At the pulsed mode, the output energyincreased linearly with the input current and decreased with pulse frequency. The threshold currentincreased with increasing pulse frequency increasing. The maximum output energy from the thin disclaser was 0.98 μJ at 1.3 kHz frequency, with 0.49A. A minimum threshold current for CW mode ofoperation. The maximum output power from the disc laser was 22 mW.